Oral pharmacological chaperone migalastat compared with enzyme replacement therapy in Fabry disease: 18-month results from the randomised phase III ATTRACT study. Issue 4 (10th November 2016) - Hughes, Derralynn A; Nicholls, Kathleen; Shankar, Suma P; Sunder-Plassmann, Gere; Koeller, David; Nedd, Khan; Vockley, Gerard; Hamazaki, Takashi; Lachmann, Robin; Ohashi, Toya; Olivotto, Iacopo; Sakai, Norio; et al.
Abstract : Background: Fabry disease is an X-linked lysosomal storage disorder caused by GLA mutations, resulting in α-galactosidase (α-Gal) deficiency and accumulation of lysosomal substrates. Migalastat, an oral pharmacological chaperone being developed as an alternative to intravenous enzyme replacement therapy (ERT), stabilises specific mutant ( amenable ) forms of α-Gal to facilitate normal lysosomal trafficking. Methods: The main objective of the 18-month, randomised, active-controlled ATTRACT study was to assess the effects of migalastat on renal function in patients with Fabry disease previously treated with ERT. Effects on heart, disease substrate, patient-reported outcomes (PROs) and safety were also assessed. Results: Fifty-seven adults (56% female) receiving ERT (88% had multiorgan disease) were randomised (1.5:1), based on a preliminary cell-based assay of responsiveness to migalastat, to receive 18 months open-label migalastat or remain on ERT. Four patients had non-amenable mutant forms of α-Gal based on the validated cell-based assay conducted after treatment initiation and were excluded from primary efficacy analyses only. Migalastat and ERT had similar effects on renal function. Left ventricular mass index decreased significantly with migalastat treatment (−6.6 g/m 2 (−11.0 to −2.2)); there was no significant change with ERT. Predefined renal, cardiac or cerebrovascular events occurred in 29% and 44% of patients in the migalastat and ERT groups, respectively. Plasma globotriaosylsphingosine remained low and stable following the switch from ERT to migalastat. PROs were comparable between groups. Migalastat was generally safe and well tolerated. Conclusions: Migalastat offers promise as a first-in-class oral monotherapy alternative treatment to intravenous ERT for patients with Fabry disease and amenable mutations. Trial registration number: NCT00925301 ; Pre-results.